1978
DOI: 10.1007/bf01448351
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' assessments of term and pre-term infants with respiratory distress syndrome: Reliability and predictive validity

Abstract: Assessments of term and preterm RDS infants were made by mothers on an adaptation of the Brazelton scale. The mother's assessments were not significantly different from those assessments made by trained clinicians, and both mothers and clinicians assigned less optimal ratings to the preterm infants. These ratings were correlated with Bayley motor scores at eight months. Mothers' assessments of infant temperament were made at four and eight months. These temperament ratings were significantly correlated with ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The relative unresponsiveness of the preterm infant and his or her relatively less developed repertoire of coos and smiles, frequent gaze aversion, and fussiness may be perceived as aversive by the mother, as might the often noted fragile features of the preterm infant. In addition, the difficult temperaments of these infants (as evaluated by the parents; Field, Hallock, Dempsey, & Shuman, 1978) may contribute to a parental perception of these infants as being somewhat aversive. All of these aversive behaviors may be generalized by the parents to even those situations in which the infant is not displaying aversive behaviors.…”
Section: Theories Regarding Disturbed Interactionsmentioning
confidence: 98%
“…The relative unresponsiveness of the preterm infant and his or her relatively less developed repertoire of coos and smiles, frequent gaze aversion, and fussiness may be perceived as aversive by the mother, as might the often noted fragile features of the preterm infant. In addition, the difficult temperaments of these infants (as evaluated by the parents; Field, Hallock, Dempsey, & Shuman, 1978) may contribute to a parental perception of these infants as being somewhat aversive. All of these aversive behaviors may be generalized by the parents to even those situations in which the infant is not displaying aversive behaviors.…”
Section: Theories Regarding Disturbed Interactionsmentioning
confidence: 98%
“…This is the first study that has reported that mothers and NBAS examiners agreed in their estimates of infants' orientation skills. Field and others (Field et al, 1978;Standley et al, 1981) found that mothers underestimate their infants' sociability in comparison to NBAS examiners. One explanation for the varying results is that Field et al's (1978) observations were based upon a more objective assessment of maternal perceptions.…”
Section: Orientationmentioning
confidence: 98%
“…Agreement between mothers' and clinicians' assessments of infant behaviors is one valid index of objectivity. Field and colleagues (Field, Hallock, Dempsey, & Shuman, 1978) examined mothers' and NBAS testers' perceptions of premature infants' and full-term infants' behaviors along dimensions of the NBAS. Mothers' judgments were based upon their administration of the Mother's Assessment of the Behavior of Her Infant (MABI), a modified version of the Brazelton.…”
Section: Perceptions Of Neonatal Beha Viorsmentioning
confidence: 99%
“…Such characteristics are assumed not to be restricted to performance on specific tasks but to be generic in nature and observable across a variety of situations. A review of research on various domains of infant development (Simeonsson, Huntington, & Parse, 1980) has indicated that behavioral characteristics (Field, Hallock, Dempsey, & Shuman, 1978;Matheny, Dolan, & Wilson, 1974) have potential value to enhance assessment.…”
Section: Behavioral Characteristicsmentioning
confidence: 99%